Risk factors for the development of knee osteoarthritis - Kasjmir, Yoga I; Nasution, A R; Daud, Rizasyah (Indonesian Rheumatology Association, 2009)
Objective. This article presents case control study conducted at the Rheumatology Outpatient Unit, Department of Internal Medicine, Cipto Mangunkusumo Hospital. The aim of this study was to determine several risk factors for the development of knee osteoarthritis (OA) at Rheumatology out-patient unit Department of InternalMedicine, Cipto Mangunkusumo Hospital.Method. This study used a case control design. Subjects were divided into two groups, case group and control group. The case group included all patients who had kneecomplaints that fulfi lled the 1990 American College of Radiology criteria while the control group included patients randomly chosen from visitors of the RheumatologyOutpatient Unit of Cipto Mangunkusumo Hospital who did not complain of knee pain and had been proven of not suffering OA by physical and radiological examinations. A similar questionnaire was designed for both groups. After filling out the questionnaire, both groups were examined physically and radiologically. The risk factors were analyzed using logistic regression.Results. We included 127 patients in the case group and 102 in the control group. In the case group, there were 95 women (74.80 %) and 32 men (25.20%) while the control group consisted of 69 women (67.65%) and 33 men (32.35%). From the analysis of several risk factors, there were signifi cant differences between the case and control groups such as weight (p < 0.0001 df 3), prior history of overweight or obesity (x2 = 21.255, df 1, p < 0.0001), knee trauma (p = 0.0002), and kneel down activity (p < 0.0001). There was also a signifi cant difference of smoking habit between the case group and the control group (p < 0.0001). Duration of smoking cessation was also signifi cantly different between the case group and controlgroup (t = 2.315, df 45, p = 0.0252). From the multivariate analysis, it was found that age, kneel down activity, prior obesity condition, interval between knee trauma and onset of OA, smoking habit, and duration of smoking cessation had a signifi cant correlation with knee OA.Conclusion. Age, prior history of overweight or obesity, kneeling, and interval between knee trauma and onset of OA were risk factors of knee OA. Smoking was a negative risk factor for knee OA. The protective effect of smoking was infl uenced by the duration of smoking habit and the duration of smoking cessation.